UJI POTENSI TRICHODERMA INDIGENOUS SULAWESI TENGGARA SEBAGAI BIOFUNGISIDA TERHADAP Phytophthora capsici SECARA IN-VITRO - Gusnawaty, HS; Asniah, Asniah; Taufik, Muhammad; Faulika, Faulika (Jurnal Agroteknos, 2013)
This research was conducted in the Laboratory of Plant Pest and Disease, Department of Agrotecnologi, Faculty of Agriculture, Halu Oleo University Kendari, from May to August 2013. This study aimed to evaluate potential Trichoderma isolates indigeneous Southeast Sulawesi as biofungicide against Phytophthora capsici and Fusarium oxysporum in-vitro. The potential inhibitory test used multiple testing methods on PDA medium. The research design was a completely randomized design (CRD) consisting of 11 treatments (trichoderma isolates) with three replications. Variables measured were the inhibition of trichoderm a indigeneous on the growth of P. capsici and F. oxysporum. Results of the experiment showed that the  trichoderma isolates were potential as biofungicide of P. capsici and F. oxysporum because they were able to inhibit the growth of pathogens in-vitro. All trichoderma isolates tested had the same potential as biofungicide against P. capsici, and isolate DKT, BPS, LKA, ASL, LTB, APS, DPA, LKO and DKP has the best potential as biofungicide against pathogenic F. oxysporum in-vitro. Keywords:   F.   oxysporum,   inhibitory,   indigenous   of   Southeast   Sulawesi,   P.   capsici, trichoderma